TAMBAHAN PENGHASILAN BERSYARAT (TPB) SEBAGAI WUJUD KINERJA ASN DI SETDA PROVINSI PAPUA (Administratio, 2017)
Abstract. Low ASN welfare greatly affects the performance of public services ?. This can be based on thelow payroll system. This paper intends to explain some of the payroll issues in Indonesia and how theyaffect the performance of ASN. Regional Performance Allowances as the only incentive to ASN in additionto the salary and benefits attached to Salary, overpriced benefits and transportation allowances forStructural and Functional Officials provided on the basis of attendance and performance appraisal. Thewriting is referred to in the Supplement of Conditional Income (TPB) as pergub no. 11 of 2014 in the RegionalSecretariat of Papua Province, as a manifestation of policy implementation by the governor to presumablymotivate ASN to be more disciplined and achievement in carrying out duties and responsibilities in order torealize a good public service. Key Words: Supplemental Conditional Income, ASN Performance